Syndromic Diagnosis Vs. Laboratory Diagnosis of Reproductive Tract Infections Among Married Women of Reproductive Age Group in Urban Slum of Mumbai - Mangala M Bote; Rahul C Bedre; Harsha B Solanki; Anita G Shenoy; Sudam R Suryawanshi (Medsci Publications, 2015)
Background: In most developing countries, STIs are managed syn- dromically because of lack the equipment and trained personal re- quired for etiological diagnosis of STIs. We assessed the adequacy of syndromic diagnosis of STIs, compared with laboratory diagnosis of STIs/RTIs. Methods: A community based, cross-sectional study was carried out among 466 women of reproductive age group during period of Jan 2007 to Jan 2008 at Urban Health Centre. Participants were selected by systematic random sampling. Results: In the present study, 50% of women reported symptoms related to various RTI syndromes of which most common was vagin- al discharge. However self reported symptoms correlated poorly with laboratory evidence of RTIs, with sensitivity of 55.06% and spe- cificity of 57.33%. An improvement in sensitivity from 55.06% to 82.91% was observed when RTIs were diagnosed with clinical ex- amination however specificity decreased to 53.33% from 57.33%. The sensitivity of algorithm for diagnosing cervical abnormality on clini- cal examination is low (56.04%) missing most true infections. Conclusions: The control of STIs in resource poor settings remains a major challenge. The development of simple affordable diagnostic tests that can be used for case finding is highest priority.